2017
DOI: 10.1038/srep45896
|View full text |Cite
|
Sign up to set email alerts
|

Search for ferromagnetic order in overdoped copper-oxide superconductors

Abstract: In copper-oxides that show high-temperature superconductivity (HTS), the critical temperature (Tc) has a dome-shaped doping dependence. The cause of demise of both Tc and superfluid density ns on the overdoped side is a major puzzle. A recent study of transport and diamagnetism in a large number of overdoped La2−xSrxCuO4 (LSCO) films shows that this cannot be accounted for by disorder within the conventional Bardeen-Cooper-Schrieffer theory. This brings to focus an alternative explanation — competition of HTS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
(57 reference statements)
0
6
0
Order By: Relevance
“…ARPES, STM and our own THz data, pointing to "Dynes-superconductor" physics [31][32][33][34][35] But this pair breaking does not originate from magnetic impurities [65], as it does in BCS-Abrikosov-Gorkov theory. In fact the origin of the strong residual (T→0) fermionic Drude response is likely the central mystery in overdoped cuprates.…”
Section: Extensive Pair-breaking Has Been Clearly Observed Inmentioning
confidence: 73%
See 1 more Smart Citation
“…ARPES, STM and our own THz data, pointing to "Dynes-superconductor" physics [31][32][33][34][35] But this pair breaking does not originate from magnetic impurities [65], as it does in BCS-Abrikosov-Gorkov theory. In fact the origin of the strong residual (T→0) fermionic Drude response is likely the central mystery in overdoped cuprates.…”
Section: Extensive Pair-breaking Has Been Clearly Observed Inmentioning
confidence: 73%
“…However, none of these has been observed so far in overdoped LSCO. We have also looked for hypothetical competing ferromagnetic order [64] but observed none [65]. (The same experiment also ruled out the presence of a large density of magnetic impurities.…”
Section: We See No Other Phase(s) Experimentallymentioning
confidence: 97%
“…Although d-wave superconductivity can be suppressed with FM fluctuations in cuprate superconductors 39 , careful consideration is required for the quantitative assessment of supercon-ductivity suppression. Indeed, some studies have suggested that FM fluctuations are not related to the disappearance of superconductivity in overdoped cuprates 40 .…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Competing ferromagnetic fluctuations have been proposed 77,78 and experimental evidence for 79,80 and against 81 such fluctuations has been reported. It is important to note that an alternative description of overdoped cuprates based dirty on d-wave BCS theory has been proposed 72,82 , though it has faced some rebuttal by others 81,83 .…”
Section: Discussionmentioning
confidence: 99%